The Caribou Québec Corporation: one step toward caribou conservation - Théberge, Annie (Rangifer, 2003)
The operation of Caribou Québec will be based on the general principle that the resource users (native and non-native people and communities, outfitters, sport hunters, commercial users, etc.) in collaboration with related government organizations, participate actively in conservation and management projects.